2011
DOI: 10.1007/s11218-011-9154-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of stereotype threat on test-taking behaviors

Abstract: This study examines the relationship between stereotype threat and individual test-taking behaviors. Previous research has examined the impact of stereotype threat on test scores, but little research has examined the impact of stereotype threat on the test-taking behaviors impacting those scores. Using a pre-post experimental design, stereotype threat was manipulated and test-taking behaviors (e.g., time spent per item, response changes) were measured while completing verbal ability items before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…19 Test-taking strategies appear to have no impact on answer-changing behaviors, either the number of answers changed or the gain or loss from the changes. 15,20,22 Some students have reported that they may have utilized a different test-taking strategy, rereading all exam questions versus rereading only the questions they were unsure of, for exams with limited time. 15 Cognitive styles, such as field dependence/independence, which measures for impulsivity and reflectivity, do not have an association with answer-changing behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…19 Test-taking strategies appear to have no impact on answer-changing behaviors, either the number of answers changed or the gain or loss from the changes. 15,20,22 Some students have reported that they may have utilized a different test-taking strategy, rereading all exam questions versus rereading only the questions they were unsure of, for exams with limited time. 15 Cognitive styles, such as field dependence/independence, which measures for impulsivity and reflectivity, do not have an association with answer-changing behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral variables such as test-taking skills are also affected by negative stereotypes. Test-taking skills include a variety of factors such as test-wiseness, memory, and time management on exams (Scherbaum, Blanshetyn, Marshall-Wolp, Mccue, & Strauss, 2011). Scherbaum et al (2011) examined how stereotype threat can differentially influence the test-taking behaviors of students of color.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Test-taking skills include a variety of factors such as test-wiseness, memory, and time management on exams (Scherbaum, Blanshetyn, Marshall-Wolp, Mccue, & Strauss, 2011). Scherbaum et al (2011) examined how stereotype threat can differentially influence the test-taking behaviors of students of color. The authors evaluated the impact of stereotype threat on time management (e.g., amount of time spent on each question) and response choice behaviors (e.g., changing answers).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations